Passing on the hot potato: The use of ETFs by open-ended funds to manage redemption requests - Lennart Dekker; Luis Molestina Vivar; Christian Weistroffer (European Central Bank (ECB), 2024)
This paper examines the use of ETFs by open-ended investment funds in the euro area to manage liquidity. We find that during the COVID-19 market turmoil, investment funds were the most run-prone investor type in the market for ETFs. We also show that open-ended funds that faced larger outflows in March 2020 scaled down their ETF holdings by a larger amount. These results are consistent with open-ended funds passing on their outflows to the ETF shares they held. Since open-ended investment funds are the largest group of ETF investors in the euro area, their trading can materially impact primary ETF flows during times of stress.
Keywords: G01; G11; G23; 330; Exchange-traded funds; cross-fund holdings; liquidity management; COVID-19 pandemic